Shared decision making between patients with Fabry disease and physicians in Japan: An online survey - Natsuko Inagaki; Mio Tsuchiya; Kazuki Otani; Takeo Nakayama (Molecular Genetics and Metabolism Reports, 2022)
Background: Fabry disease is a rare, progressive genetic lysosomal disorder that can cause multisystem organ dysfunction. With increasing treatment options for Fabry disease, it is imperative that patients discuss and select treatment plans in conjunction with their physicians. Although shared decision making (SDM) should be recommended for clinical decision making in disease management, evidence is limited as to how patients in Japan are involved in the choice of their Fabry disease treatment and if other gaps exist with physicians in the perception of Fabry disease management. Objective: The main objective of the study was to assess the degree of agreement between patients and treating physicians in the SDM process as assessed by the SDM-Q-9 and SDM-Q-Doc questionnaires. In parallel, this study also investigated other factors that might impact the SDM process. Methods: This was a cross-sectional web-based questionnaire survey of Japanese patients with Fabry disease and their treating physicians conducted from February 2021 to June 2021. Online surveys were developed for patients and physicians, consisting of seven items, including the Japanese version of the 9-item SDM Questionnaire for patients (SDM-Q-9) and physicians (SDM-Q-Doc). Physicians were divided into two cohorts: non-paired and paired with patients. Only the paired cohort physicians answered the SDM questionnaire. Results: A total of 99 physicians and 30 patients answered the respective questionnaires. Among these, 13 physicians were included in a paired SDM analysis with patients. Mean (standard deviation [SD]) patient age at diagnosis of Fabry disease was 47.5 (15.8) years, and 14 (46.7%) were male. Both physicians in the paired cohort and patients considered patient-reported outcomes (both 76.7%) and the findings from laboratory testing as important (90.0% and 60.0% respectively). However, regarding symptoms that affect quality of life of patients, perception gaps were identified in that physicians in the paired cohort placed less importance on patient-reported outcome-related symptoms such as sweating abnormalities and gastrointestinal symptoms than their patients (0% [0/17] and 44.4% [8/18], 11.8% [2/17] and 38.9% [7/18], respectively). In the paired analysis, there was no significant difference in total SDM score between patients and physicians (p = 0.82). However, the largest discordance in perception between patients and physicians was identified for the explanation of the advantages and disadvantages of the treatment options (weighted Kappa coefficient = 0.14). Conclusion: This survey revealed a gap in the perception of disease burden affecting patients' quality of life, and a recognition gap between physicians and patients when they discussed the advantages and disadvantages of treatment options. To improve the SDM process in Fabry disease management and treatment, practical solutions for bridging these gaps should be considered.